“The Founder and Father of his Empire”: Voltaire on the Peace of Nystad and the Imperial Status of Russia - S. A. Mezin (Vestnik MGIMO-Universiteta)
The purpose of the paper is revealing the peculiarities of Voltaire’s views on the last stage of the Northern War, ended by the Treaty of Nystad, as well as presenting the specific character of the great enlightener’s evaluation of the Russian empire and its historical role. The author finds out, why Voltaire, condemning fascination with the history of wars and kings, in his two works: «The History of Charles XII» and «The History of the Russian Empire under Peter the Great» paid great attention to the Northern War and Peter I’s participation in it.The reasons of the French historian interest to the named subject are viewed in terms of the modern methods of historical analysis, «philosophical» basis of his views on war and civilization, features of historical presentation.The paper shows Voltaire’s change in attitude on interpretation of the military historical subjects, first covered in «The History of Charles XII» and then in «The History of the Russian Empire under Peter the Great». The focus of the paper is on the up to the present-day controversial issue, whether Peter I was involved in Gorth–Alberoni conspiracy, aimed at the complete political change in the appearance of Europe. The 18th century historian ultimately came to the conclusion that the Tsar had made use of Gorth’s plans as a tactic means for solving his own foreign policy problems. This point of view is shared by many contemporary historians. Peter I’s declaring Emperor was the direct consequence of victorious end of the Northern War. It was found that Voltaire drew a more optimistic picture of Peter I’s imperial title recognition, than it actually was. According to Voltaire, the specific feature of the Russian Empire, created by Peter I, lies in the fact that it was a self-civilizing empire, bringing enlightenment on the neighboring «barbaric» peoples.The author of the paper, reviewing specific cases, arrives at a conclusion, that Voltaire’s works of high confidence for their time took a worthy standing in the world historiography of the Petrine era, due to a wide range of sources, the historian’s ability for their critical assessment, his seeking to maintain a certain evaluation independence in the description of events from different perspectives, his commitment to historical truth, his talent of a writer.The work is carried out within the project, aimed at publishing a first complete scientific edition of «The History of the Russian Empire under Peter the Great» in Russian.